Energy metabolism in osteoclast formation and activity. (October 2016) - Lemma, Silvia; Sboarina, Martina; Porporato, Paolo E.; Zini, Nicoletta; Sonveaux, Pierre; Di Pompo, Gemma; Baldini, Nicola; Avnet, Sofia
Graphical abstract: Abstract: Osteoclastogenesis and osteolysis are energy-consuming processes supported by high metabolic activities. In human osteoclasts derived from the fusion of monocytic precursors, we found a substantial increase in the number of mitochondria with differentiation. In mature osteoclasts, mitochondria were also increased in size, rich of cristae and arranged in a complex tubular network. When compared with immature cells, fully differentiated osteoclasts showed higher levels of enzymes of the electron transport chain, a higher mitochondrial oxygen consumption rate and a lower glycolytic efficiency, as evaluated by extracellular flux analysis and by the quantification of metabolites in the culture supernatant. Thus, oxidative phosphorylation appeared the main bioenergetic source for osteoclast formation. Conversely, we found that bone resorption mainly relied on glycolysis. In fact, osteoclast fuelling with galactose, forcing cells to depend on Oxidative Phosphorylation by reducing the rate of glycolysis, significantly impaired Type I collagen degradation, whereas non-cytotoxic doses of rotenone, an inhibitor of the mitochondrial complex I, enhanced osteoclast activity. Furthermore, we found that the enzymes associated to the glycolytic pathway are localised close to the actin ring of polarised osteoclasts, where energy-demanding activities associated with bone degradation take place. In conclusion, we demonstrate that the energy required for osteoclast differentiation mainly derives from mitochondrial oxidative metabolism, whereas the peripheral cellular activities associated with bone matrix degradation are supported by glycolysis. A better understanding of human osteoclast energy metabolism holds the potential for future therapeutic interventions aimed to target osteoclast activity in different pathological conditions of bone.